2003
DOI: 10.1001/archpsyc.60.12.1218
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Week, Double-blind Comparison of Olanzapine vs Haloperidol in the Treatment of Acute Mania

Abstract: These data suggest that olanzapine does not differ from haloperidol in achieving overall remission of bipolar mania. However, haloperidol carries a higher rate of extrapyramidal symptoms, whereas olanzapine is associated with weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
102
4
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(124 citation statements)
references
References 35 publications
15
102
4
2
Order By: Relevance
“…From this review, haloperidol had the highest risk for movement disorders. These results are consistent with head-to-head comparison studies of haloperidol versus atypical agents in BPD 45,46 and schizophrenia. 47,48 However, it is also possible that the unnecessarily high doses of haloperidol being used in these studies might play a role.…”
Section: Discussionsupporting
confidence: 87%
“…From this review, haloperidol had the highest risk for movement disorders. These results are consistent with head-to-head comparison studies of haloperidol versus atypical agents in BPD 45,46 and schizophrenia. 47,48 However, it is also possible that the unnecessarily high doses of haloperidol being used in these studies might play a role.…”
Section: Discussionsupporting
confidence: 87%
“…94,95,[100][101][102]105,106 Data from studies longer than 12 weeks are limited. A total of 4 studies have reported on monotherapy with atypical antipsychotics for a period greater than 12 weeks, 3 with olanzapine and 1 with aripiprazole, with 26-week and 100-week results being reported separately.…”
Section: Overview Of Efficacy Evidence From Key Clinical Trialsmentioning
confidence: 99%
“…The AE profiles of quetiapine and olanzapine in the bipolar depression studies reflect those already established in the bipolar mania studies, with the exception that quetiapine is associated with EPS significantly more often than placebo in depression trials. In terms of effects on metabolic parameters, all of the atypical antipsychotics have been associated with weight gain [92][93][94][95][96][97][98][99][100][101][102]104,106 ; however, levels varied according to the different atypical antipsychotics. 66,[93][94][95]97,106 Compared with haloperidol, atypical antipsychotics (olanzapine and quetiapine) were associated with lower rates of akathisia in monotherapy trials of 12 weeks.…”
Section: Overview Of Safety Evidence From Clinical Trialsmentioning
confidence: 99%
See 2 more Smart Citations